2022
DOI: 10.3389/fcimb.2022.871135
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic-di-AMP Phosphodiesterase Elicits Protective Immune Responses Against Mycobacterium tuberculosis H37Ra Infection in Mice

Abstract: Many antigens from Mycobacterium tuberculosis (M. tuberculosis) have been demonstrated as strong immunogens and proved to have application potential as vaccine candidate antigens. Cyclic di-AMP (c-di-AMP) as a bacterial second messenger regulates various bacterial processes as well as the host immune responses. Rv2837c, the c-di-AMP phosphodiesterase (CnpB), was found to be relative to virulence of M. tuberculosis and interference with host innate immune response. In this study, recombinant CnpB was administer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 79 publications
(130 reference statements)
0
1
0
Order By: Relevance
“…42,43 In this study, we established an H37Ra infection model and demonstrated how the bacterium modifies host immunity and lipid metabolism via miR-144-3p. Although H37Ra and H37Rv have a strong genetic link and perform substantially comparable roles, 43,44 the virulence of Mtb may result in different immune escape responses to the host. 45,46 Given the regulatory mechanism described here, it remains to be determined whether the involvement of miR-144-3p during H37Ra infection can be applied to H37Rv or animal experiments to generate greater physiological significance.…”
Section: ■ Discussionmentioning
confidence: 99%
“…42,43 In this study, we established an H37Ra infection model and demonstrated how the bacterium modifies host immunity and lipid metabolism via miR-144-3p. Although H37Ra and H37Rv have a strong genetic link and perform substantially comparable roles, 43,44 the virulence of Mtb may result in different immune escape responses to the host. 45,46 Given the regulatory mechanism described here, it remains to be determined whether the involvement of miR-144-3p during H37Ra infection can be applied to H37Rv or animal experiments to generate greater physiological significance.…”
Section: ■ Discussionmentioning
confidence: 99%